Kepadatan Bulu Babi (Diadema setosum) Pada Ekosistem Terumbu Karang Di Karang Kering Perairan Bedukang Kabupaten Bangka - Sema Al-Risqia; Kurniawan Kurniawan; Indra Ambalika (Journal of Tropical Marine Science, 2021)
Bedukang waters have a 35,9% karang kering reef ecosystem cover. Coral reefs function as spawning grounds for marine biota and as a source of germplasm. The presence of Diadema setosum in coral reef ecosystems can affect the ecolohical balance in the coral reef ecosystem of a waters. The research aims to analyze data and information on the density of Diadema setosum in coral reef ecosystems, to analyze the association of Diadema setosum density with habitat characteristics in coral reef ecosystems, as preliminary data on Diadema setosum populations in Bedukang waters. The research was conducted on March 2019 in the dry coral waters of Bedukang. Belt Transect method was used for data retrieval of Diadema setosum and Line Intercept Transect for coral reef data retrieval. The results of this research was Diadema setosum density of 3708 individuals/ha. The percentage of coral cover on Bedukang waters is in good condition with a value of 55.79%. The associations between the density of Diadema setosum with the coral lifeform Acropora Branching (ACB), Acropora Digitate (ACD), Coral Submassive (CS), Turf Algae (TA), dan Other (OT).